The variants and meanings of Malay motif ornamentation in the urban context: a case study of Putrajaya - Kamaruddin, Zumahiran; Jahn Kassim, Puteri Shireen; Abdullah, Alias (Malaysian Institute Of Planners, 2020)
As Malaysia’s new satellite city, types of Malay motif and meanings in Putrajaya have been abstracted and used as design motifs and ornamentation for the quest of local identity. However, it is uncertain whether the placement of such components, which is sometimes difficult to comprehend, gives the premises a sense of identity. Therefore, this study aims to identify the variants, meanings and applications of these motifs in the ornamentation of public buildings in the urban context leading to its character and identity formation. The researchers had conducted on-site surveys and photographic documentation, and semi-structured interviews for data collection. Using Putrajaya as a case study, a visual descriptive and interpretative analyses was undertaken to analyse the underlying basis in terms of various plants from natural surrounding and transformations into the new depiction of motifs. The analyses revealed two distinctive types of Malay motifs depictions found in the building components with the tangible and intangible qualities that articulate their compositional order. The Malay urban character involves the depictions of abstract motifs incorporating local Malay cultural elements. Plant-based motifs dominate the ornamentation, which have its meaning and characteristics. The physical and practical nomenclatures of the motifs are indicators of continuity of tradition in the urban buildings. Further research is necessary to investigate the people’s perception of these abstracted motifs as ornamentation in the interior and exterior spaces of the public buildings.